Implementation of Information Commission Regulation Number 1 of 2018 Concerning Village Public Information Service Standards in Independent Villages - Hasan, Lufti Faurusal; Rusdiono; Jumadi; Martoyo; Musa, Pabali (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This thesis aims to provide an understanding of how the Regulation of the Information Commission (PerKI) Number 1 of 2018 concerning the Standards of Public Information Services (SLIP) for villages is implemented in self-reliant villages in Sungai Raya District, Kubu Raya Regency, as an elaboration of Law Number 14 of 2018 on Public Information Disclosure (KIP). The main problem identified is that the implementation of PerKI Number 1 of 2018 regarding Village SLIP has not been optimal. Public information services managed by the Village Information and Documentation Management Officer (PPID) have not fully complied with the established Village SLIP, and no derivative regulation at the regency level provides technical support to strengthen village PPID management. This study seeks to understand the situation and analyze the supporting and inhibiting factors affecting the institutional condition of Village PPID in self-reliant villages in Sungai Raya District, Kubu Raya Regency, West Kalimantan Province, in implementing PerKI Number 1 of 2018. The findings show that the implementation has not run effectively. Organizationally, Village PPID as the implementer has not performed its role as expected due to limited apparatus resources overlapping with public service duties. Stakeholders’ interpretation of policy objectives has not been fully conveyed, and practical implementation has not consistently followed PerKI Number 1 of 2018. This study recommends optimizing the role of Village PPID through regional agencies responsible for public information disclosure, improving the capacity of village apparatus through socialization, training, or technical guidance, and issuing derivative regulations as operational guidelines for translating PerKI Number 1 of 2018 concerning Village SLIP.